2021
DOI: 10.1080/09638288.2021.1936661
|View full text |Cite
|
Sign up to set email alerts
|

Associations between positive treatment outcome expectations, illness understanding, and outcomes: a cohort study on non-operative treatment of first carpometacarpal osteoarthritis

Abstract: Purpose: More positive outcome expectations and illness perceptions are associated with better outcomes for patients with several osteoarthritic orthopedic conditions. However, it is unknown whether these factors also influence outcomes of non-operative treatment for first carpometacarpal osteoarthritis (CMC-1 OA). Therefore, we assess the role of pre-treatment outcome expectations and illness perceptions in reports of pain and hand function 3 months after non-operative treatment for CMC-1 OA. Materials and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…The mental health screening tool explained a substantial part of the variance in pain and hand function at baseline and 3 months. This highlights, in line with other studies [3-5, 8, 9, 12, 14-16, 18, 19, 25, 28, 30, 31, 33, 35, 36], the importance of mental health and its relation to treatment decisions and outcomes. The models with only the screening tool items performed nearly as well as the models using the full mental health measures (that is, the entire PCS, PHQ-4, and B-IPQ), which further substantiates the validity of our tool.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mental health screening tool explained a substantial part of the variance in pain and hand function at baseline and 3 months. This highlights, in line with other studies [3-5, 8, 9, 12, 14-16, 18, 19, 25, 28, 30, 31, 33, 35, 36], the importance of mental health and its relation to treatment decisions and outcomes. The models with only the screening tool items performed nearly as well as the models using the full mental health measures (that is, the entire PCS, PHQ-4, and B-IPQ), which further substantiates the validity of our tool.…”
Section: Discussionsupporting
confidence: 90%
“…In musculoskeletal healthcare, patient mental health has gained attention in recent years. Numerous studies have demonstrated that mental health factors influence symptoms, outcomes, and treatment choices [3-5, 8, 9, 12, 14-16, 18, 19, 25, 28, 30, 31, 33, 35, 36]. For example, patients with thumb-base osteoarthritis scheduled for surgery have worse psychologic profiles than their nonsurgical counterparts [37], suggesting that domains of mental health play an important role in choosing between surgical and nonsurgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that more-positive outcome expectations are associated with better treatment outcomes [ 1 , 5 , 6 , 8 , 23 , 27 , 33 ], and there is an interest in positively modifying outcome expectations to improve treatment outcomes. However, little was known about factors independently associated with outcome expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies suggested expectations of medical treatments are already too high and should be tempered by the clinician to cultivate realistic expectations for the patient [ 13 , 19 , 24 , 35 ], several meta-analyses have found that patients with more-positive pretreatment expectations achieve better outcomes [ 1 , 5 , 6 , 27 ]. Additionally, in patients treated for hand or wrist conditions, more-positive expectations have been reported to be associated with better outcomes [ 8 , 23 , 33 ]. In addition, positive expectations of the treatment outcomes are considered a key mechanism of placebo effects [ 20 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…We fully agree with the letter authors on the importance of considering the psychological profiles of patients when predicting outcomes after surgical treatment of the first carpometacarpal with osteoarthritis (CMC-1 OA). Our research group previously published on the association between psychological profile and patientreported outcome measures before and after nonsurgical treatment for CMC-1 OA [3,9,10]. We therefore included several psychological variables as possible predictors for our models, including the PHQ-4 for depression and anxiety.…”
Section: To the Editormentioning
confidence: 99%